Work-Related conflicts between UiTM Sarawak's course coordinators and lecturers / Aiza Johari, Affidah Morni and Dayang Faridah Abang Bohari - Johari, Aiza; Morni, Affidah; Abang Bohari, Dayang Faridah (Research Management Institute (RMI), 2012)
This study aims to identify and compare the possible causes and effects of work-related conflicts as well as the conflict management styles between the Course Coordinators and lecturers of UiTM Sarawak. The study looked at UiTM Sarawak's Academic Staff, through the lens of 23 Course Coordinators and 76 lecturers from various faculties. A different set of adapted questionnaire was distributed to the two groups mentioned and the data was analysed using SPSS Version 20. The findings revealed that most of the Coordinators and many of the lecturers did not face many problems in the six identified factors of workplace conflict: Communication, Coordination and Organisation, Personality, Leadership, Commitment and Collaboration. The Coordinators and lecturers were able to communicate well with one another; there were very few issues of personality clash, the Coordinators' leaderships were well acknowledged and most of them worked well as a team. Negotiation is perceived to be the key to hinder workplace conflict. In relation to Coordination and Organisation, the Coordinators claimed that they did not select particular person in delegating task but their responses to the statement whether they had someone in mind when assigning task indicated otherwise. As for the effects of workplace conflict, most of them were able to retain their professionalism in times of conflict. Consequently, conflict was seen not to interfere with the existing unity and harmony in the organisation. In contrast, many lecturers felt personally demotivated during conflict while very few Coordinators experienced the same way. Likewise, more than half of both groups perceived conflict to be the barrier in achieving organizational tasks and goals. In conflict management, collaborative method seems to be most popular among both groups as this method requires both parties to work together in resolving a problem. The findings of this study are believed to help create better understanding and cooperation between the lecturers and the Course Coordinators; hence improving the working environment and reducing workplace conflict.